(untitled) (Revista Española de Fisiología, 1969)
Progress curves of the rate of NADH production with NAD+-free D-glyceral-dehyde 3-phosphate dehydrogenase from rabbit skeletal muscle were markedly biphasic with final steady-state rates directly proportional to initial enzyme concentration. This work suggests that there is a change in specific activity and, furthermore, that the enzymic activity may be restored to a value approaching the original on readdition of NAD+. The studies made by gel filtration, electrophoresis and ultracentrifugation are consistent with the hypothesis that the molecular weight of the NAD+-free enzy me is similar to that of the native enzyme and that reactivation by NAD+ involves a slow transition between two tetrameric conformers. A variety of possible effectors were also studied and it was observed that NAD+, NADH and D-glyceraldehyde 3-phosplia- te reactivated the enzyme and abolished the biphasic response. ATP removed the biphasicity but produced a marked de gree of inhibition of the steady-state rate. No effect was observed with Pi, ADP, AMP, 2-mercaptoethanol, Na+, K+, Mg2+ or Ca2+; 3-phosphoglycerate and NADP produced partial reactivation.